Arabidopsis LSH10 transcription factor and OTLD1 histone deubiquitinase interact and transcriptionally regulate the same target genes - Mi Sa Vo Phan; Ido Keren; Phu Tri Tran; Moshe Lapidot; Vitaly Citovsky (Communications Biology, 2023)
The plant histone deubiquitinase, OTLD1, interacts with the Arabidopsis transcription factor, LSH10, and both transcriptionally regulate a set of common target genes.